Aluminum oxide nucleation in the early stages of atomic layer deposition on epitaxial graphene. (November 2020) - Schilirò, E.; Lo Nigro, R.; Panasci, S.E.; Gelardi, F.M.; Agnello, S.; Yakimova, R.; Roccaforte, F.; Giannazzo, F.
Abstract: The nucleation and growth mechanism of aluminum oxide (Al2 O3 ) in the early stages of atomic layer deposition (ALD) on monolayer epitaxial graphene (EG) on silicon carbide (4H–SiC) has been investigated by atomic force microscopy (AFM), conductive-atomic force microscopy (C-AFM) and Raman spectroscopy. Differently than for other types of graphene, a large and uniform density of nucleation sites was observed in the case of EG and ascribed to the presence of the buffer layer at EG/SiC interface. The deposition process was characterized by Al2 O3 island growth in the very early stages, followed by the formation of a continuous Al2 O3 film (∼2.4 nm thick) after only 40 ALD cycles due to the islands coalescence, and subsequent layer-by-layer growth. The electrical insulating properties of the deposited ultrathin Al2 O3 films were demonstrated by nanoscale current mapping with C-AFM. Raman spectroscopy analyses showed low impact of the ALD process on the defect's density of EG. The EG strain was also almost unaffected by the deposition in the regime of island growth and coalescence, whereas a significant increase was observed after the formation of a compact Al2 O3 film. The obtained results can have important implications for device applications of epitaxial graphene requiring ultra-thin high-k insulators. Graphical abstract: Image 1